Characterisation of Bergeyella spp. isolated from the nasal cavities of piglets. (April 2018) - Lorenzo de Arriba, M.; Lopez-Serrano, S.; Galofre-Mila, N.; Aragon, V.
Highlights: Bergeyella porcorum and Bergeyella zoohelcum were isolated from the nasal cavities of healthy piglets. Eleven genotypes of Bergeyella spp. were identified. B. porcorum and B. zoohelcum were able to adhere to epithelial cells. B. porcorum and B. zoohelcum exhibited serum and phagocytosis resistance. B. porcorum and B. zoohelcum exhibited multiple drug resistance. Abstract: The aim of this study was to characterise bacteria in the genus Bergeyella isolated from the nasal passages of healthy piglets. Nasal swabs from 3 to 4 week-old piglets from eight commercial domestic pig farms and one wild boar farm were cultured under aerobic conditions. Twenty-nine Bergeyella spp. isolates were identified by partial 16S rRNA gene sequencing and 11 genotypes were discriminated by enterobacterial repetitive intergenic consensus (ERIC)-PCR. Bergeyella zoohelcum and Bergeyella porcorum were identified within the 11 genotypes. Bergeyella spp. isolates exhibited resistance to serum complement and phagocytosis, poor capacity to form biofilms and were able to adhere to epithelial cells. Maneval staining was consistent with the presence of a capsule. Multiple drug resistance (resistance to three or more classes of antimicrobial agents) was present in 9/11 genotypes, including one genotype isolated from wild boar with no history of antimicrobial use. In conclusion, Bergeyella spp. isolates from the nasal cavities of piglets showed some in vitro features indicative of a potential for virulence. Further studies are necessary to identify the role of Bergeyella spp. in disease and within the nasal microbiota of pigs.